Mindfulness dengan prokrastinasi akademik siswa Madrasah Tsanawiyah (SUKMA : Jurnal Penelitian Psikologi, 2022)
Students are part of the field of education and are never separated or avoided from learning activities and responsibility to complete academic assignments. This study aims to determine the relationship between mindfulness and academic procrastination in class VIII students of MTs Roudlotun Nasyiin. . The population of this study were students of MTs Roudlotun Nasyiin class VIII A, B, and C, totaling 88 students. The research participants totaled 72 students. The research instrument used a Likert scale questionnaire with four answer choices, for the procrastination scale there were 21 valid statement items with reliability (α = 0.852) and for the mindfulness scale there were 9 valid statement items with reliability (α = 0.722). Data analysis to test the research hypothesis is the Pearson Product Moment correlation, the results show a correlation value of rxy = -0.341 with a significance value of P = 0.003; (P<0.01). These results indicate that there is a very significant negative relationship between mindfulness and academic procrastination. Siswa merupakan bagian dari bidang pendidikan dan tidak pernah terlepas atau terhindarkan dari kegiatan belajar dan kewajiban untuk menyelesaikan tugas akademik. Penelitian ini memiliki tujuan untuk mengetahui hubungan antara mindfulness dengan prokrastinasi akademik pada peserta didik kelas VIII MTs Roudlotun Nasyiin. . Populasi penelitian ini adalah peserta didik MTs Roudlotun Nasyiin kelas VIII A, B, dan C yang berjumlah 88 siswa. Partisipan penelitian berjumlah 72 siswa. Instrumen penelitian menggunakan kuisioner skala likert dengan empat pilihan jawaban, untuk skala prokrastinasi terdapat 21 aitem pernyataan valid dengan reliabilitas (α = 0,852) dan untuk skala mindfulness terdapat 9 aitem pernyataan valid dengan reliabilitas( α = 0,722). Analisa data untuk menguji hipotesis penelitian adalah korelasi Pearson Product Moment, didapatkan hasil nilai korelasi rxy = -0,341 dengan nilai signifikasi P = 0,003 ; (P<0,01). Hasil tersebut menunjukkan bahwa ada hubungan negatif yang sangat signifikan antara mindfulness dengan prokrastinasi akademik.